Biological inheritance and the social order in late-Victorian fiction and science - Berezowsky, Sherrin (My University, 2011)
This dissertation investigates the heightened interest in heredity as a kind of biological inheritance that arises after the publication of Charles Darwin’s On the Origin of Species (1859) and how this interest intersects with concerns about class mobility and the shifting social order. Within this framework, this project considers how heredity became a means of organizing and regulating bodies in keeping with what Michel Foucault terms biopower. It unearths the cultural work within literary and scientific writings as they respond to narratives of self-help and self-improvement by imagining heredity as a means of stabilizing the social order, and by extension the nation, at the very moment that it was undergoing significant change. In studying diverse texts, this project highlights the shared ideological concerns behind both literary and scientific narratives.
Keywords: English literature; nineteenth century; Victorian; heredity; inheritance; science; class